A Radiation Hardened Mutually Compensated Mobility and Threshold Voltage Reference Approach. - Nugent, Brian. (2017)
Abstract: Microelectronics that leave the earth's magnetosphere are exposed to the natural radiation environment and are subject to effects not experienced by terrestrial microelectronics. Device characteristic degradation including off state leakage current, reduced transconductance, and reduced threshold voltage are all potential consequences of being exposed to the natural radiation environment. It would benefit the designer to make these devices radiation hardened. Voltage references are used to provide accurate and stable voltages over a wide range of temperatures and they are crucial to analog integrated circuits (ICs). A radiation hardened by design (RHBD) mutually compensated mobility and threshold voltage reference was designed and tested. Mobility and threshold voltage decrease with increasing temperature. The technique of mutual compensation of mobility and threshold voltage cancels these effects for a given temperature and establishes a zero temperature coefficient (ZTC) for a diode connected MOS. It was found that linearly combining the output voltages of a diode connected NMOS and PMOS that implement this technique achieve a thermally stable voltage reference superior to either the NMOS or PMOS alone.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Electrical Engineering.; Advisor: Sameer Sonkusale.; Committee: Sameer Sonkusale, Valencia Koomson, and Rob Bousquet.; Keyword: Electrical engineering.